Collective efficiency and commons in local productive systems - Marco Bellandi (REGION, 2021)
This paper goes back to the topic of collective efficiency (CE) in localproductive systems and paths of territorial development. In general terms, such CEneeds the integration of markets mechanisms with systemic conditions that have natureof public goods. The discussion of an extended framework of specific public-like goodshelps unearthing related important commons' features, as the involvement of communitiesof local agents may be implied in their provision, use, and regulation. The paper aimsat giving a solid foundation to the study of such features, and to show how the samefoundation helps shedding light on various topics related to CE, commons, and territory
Keywords: 330; collective efficiency; local productive systems; industrial districts; territorial development; specific public goods; commons